ROLL PAPER HOLDER - MORI YASUBUMI; YOKOZEKI TAKASHI; OSHIMA HIROAKI (2021)
To provide a roll paper holder which holds paper fed by a roll body so that it is easy to take the paper out.SOLUTION: A roll paper holder 1 includes: a body 10 which has a housing part 11 housing a roll body 100 composed of long-sized paper 101; and a cover member 20 openably/closably covering the housing part 11. The body 10 is provided with: a cutter 30 arranged between a feed roller 12 and a holding roller 13; and a drive unit which drives the feed roller 12, the holding roller 13, and the cutter 30. The cover member 20 is provided with a pressing roller 24 facing the holding roller 13 when closed. The drive unit performs synchronous rotation driving of the feed roller 12 and the holding roller 13 and carries the paper 101, and then operates the cutter 30 to cut paper 101, so that the cut paper 101 is held between the holding roller 13 and the pressing roller 24.SELECTED DRAWING: Figure 3 【課題】 ロール体から繰り出されるペーパーを取り出し容易に保持するロールペーパーホルダを提供する。【解決手段】 長尺状のペーパー１０１からなるロール体１００を収容する収容部１１を有する本体１０と、収容部１１を開閉可能に覆うカバー部材２０とを備え、本体１０は、送りローラ１２および保持ローラ１３の間に配置されたカッター３０と、送りローラ１２、保持ローラ１３およびカッター３０を駆動する駆動装置とを備え、カバー部材２０は、閉じたときに保持ローラ１３と対向する押さえローラ２４を備えており、駆動装置は、送りローラ１２および保持ローラ１３を同期回転駆動させてペーパー１０１を搬送した後、カッター３０を作動させてペーパー１０１を切断することにより、切断されたペーパー１０１を保持ローラ１３および押さえローラ２４の間に保持するロールペーパーホルダ１である。【選択図】 図３